Statistical use in applied sport research: Methodological and ethical challenges. - Shalfawi, S. A. I. (Strength and Conditioning Journal, 2016)
One of the major issues in the field of applied sport science research is associated with researchers drawing biased conclusions caused by incorrect data analysis and/or explanations of the results. The purpose of this article is intended to address the issue from the researcher's methodological approach and ethical standpoint.